2019
DOI: 10.5267/j.msl.2019.5.023
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal intelligence and prosocial behavior among elementary school students

Abstract: This research aims to analyze the relationship between interpersonal intelligence and prosocial behavior among students of elementary school. As a case study, it takes 156 students of an elementary school in Yogyakarta Special Region, Indonesia as participants aged 10-12 years old. The result shows positive and significant correlation between interpersonal intelligence and prosocial behavior among participants, as shown by coefficient of correlation r=0.722 and p=0.000. Three aspects of interpersonal intellige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
1
2
0
4
Order By: Relevance
“…In this study, social competence and autonomy contribute predictive value to prosocial behavior and adjustment difficulties above each of the subject's personality dimensions. These results are consistent with other recent studies [82,83] and support the proposition that the CDE_9-13 has predictive capacity for socially relevant variables. People who possess socioemotional competencies are more aware of their emotions and the needs of others, maintaining more positive and satisfactory relationships and developing more likely prosocial behaviors [84].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, social competence and autonomy contribute predictive value to prosocial behavior and adjustment difficulties above each of the subject's personality dimensions. These results are consistent with other recent studies [82,83] and support the proposition that the CDE_9-13 has predictive capacity for socially relevant variables. People who possess socioemotional competencies are more aware of their emotions and the needs of others, maintaining more positive and satisfactory relationships and developing more likely prosocial behaviors [84].…”
Section: Discussionsupporting
confidence: 93%
“…Por otra parte, el estudio no sólo clarifi ca la correlación existente entre conducta prosocial e inteligencia emocional y su proporcionalidad, sino que evidencia que el elemento que mejor predice la conducta prosocial, aparte de la inteligencia emocional, es, especialmente, la dimensión interpersonal de la misma, como también ha señalado Kusumaningrum (2019) en un estudio reciente. Esto implica que aspectos como la empatía, la responsabilidad social y la habilidad para establecer relaciones interpersonales son elementos clave en el desarrollo de la conducta prosocial del alumnado de Educación Primaria.…”
Section: Discussionunclassified
“…Thus, it is confirmed that the findings support the previous research stated that prosocial conduct in the school reveal that boosting prosocial behavior are the predictor of performance than eliminating negative behavior. There are possibilities for the association between prosocial conduct and academic performance (Kusumaningrum, 2019).…”
Section: Discussionmentioning
confidence: 99%